Climate and land-use change homogenise terrestrial biodiversity, with consequences for ecosystem functioning and human well-being. Issue 2 (24th April 2019) - Newbold, Tim; Adams, Georgina L.; Albaladejo Robles, Gonzalo; Boakes, Elizabeth H.; Braga Ferreira, Guilherme; Chapman, Abbie S. A.; Etard, Adrienne; Gibb, Rory; Millard, Joseph; Outhwaite, Charlotte L.; Williams, Jessica J.
Abstract: Biodiversity continues to decline under the effect of multiple human pressures. We give a brief overview of the main pressures on biodiversity, before focusing on the two that have a predominant effect: land-use and climate change. We discuss how interactions between land-use and climate change in terrestrial systems are likely to have greater impacts than expected when only considering these pressures in isolation. Understanding biodiversity changes is complicated by the fact that such changes are likely to be uneven among different geographic regions and species. We review the evidence for variation in terrestrial biodiversity changes, relating differences among species to key ecological characteristics, and explaining how disproportionate impacts on certain species are leading to a spatial homogenisation of ecological communities. Finally, we explain how the overall losses and homogenisation of biodiversity, and the larger impacts upon certain types of species, are likely to lead to strong negative consequences for the functioning of ecosystems, and consequently for human well-being.